Colorectal endoscopic submucosal dissection: Technical advantages compared to endoscopic mucosal resection and minimally invasive surgery. (5th November 2013) - Saito, Yutaka; Yamada, Masayoshi; So, Eriko; Abe, Seiichiro; Sakamoto, Taku; Nakajima, Takeshi; Otake, Yosuke; Ono, Akiko; Matsuda, Takahisa
Abstract : Background and Aim: In recent years, the effectiveness of colorectal endoscopic submucosal dissection (ESD) has been increasingly reported. Herein, we highlight the most recent developments and technical advantages of colorectal ESD compared to EMR and minimally invasive surgery. Methods: All candidate lesions for ESD were confirmed as being intramucosal tumors by colonoscopy. Presently, the indications for colorectal ESD approved by the Japanese government's medical insurance system are early colorectal cancers with a maximum tumor size of 2–5 cm; however, many early cancers >5 cm have been treated by ESD in referral centers. Results: The primary advantage of ESD compared to endoscopic mucosal resection (EMR) is a higher en‐bloc resection rate for large colonic tumors that had previously been treated by surgery. ESD has several advantages compared to other therapeutic modalities, such as being a safer technique and providing better quality of life. For rectal cancer treatment, a longer procedure time is required for laparoscopic assisted colectomy, whereas trans‐anal resection and trans‐anal endoscopic microsurgery are more invasive than ESD with a significantly higher recurrence rate. Accordingly, ESD is the preferred choice for early colorectal cancers when there is no risk of lymph‐node metastasis. Conclusion: ESD is an effective procedure for treating non‐invasive non‐polypoid colorectal tumors. These tumors may be difficult to resect en bloc by conventional EMR. The use of ESD results in a higher en‐bloc resection rate and is less invasive than surgery.